2021
DOI: 10.1038/s41598-021-98345-6
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam CT optimisation for detection of vertical root fracture with metal in the field of view or the exomass

Abstract: Dose optimisation has been revisited in the literature due to the frequent use of cone beam computed tomography (CBCT). Although the reduction of the field-of-view (FOV) size has shown to be an effective strategy, this indirectly increases the negative effect from the exomass. The aim of this study was to evaluate the diagnostic accuracy of an optimised CBCT protocol in the detection of simulated vertical root fracture (VRF) in the presence of metal in the exomass and/or inside the FOV. Twenty teeth were endod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…is finding indicates the dominance of hypodense artifacts on the images, which can probably have a negative effect on the detection of hypodense conditions such as fracture lines in the clinical setting. However, a previous study showed that although the presence of high-density materials in the exomass negatively affected the CBCT image quality, they had no adverse effect on the diagnostic accuracy of CBCT for detection of vertical root fractures [37]. is difference is probably due to the use of different types of scanners and optimized exposure settings applied in their study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…is finding indicates the dominance of hypodense artifacts on the images, which can probably have a negative effect on the detection of hypodense conditions such as fracture lines in the clinical setting. However, a previous study showed that although the presence of high-density materials in the exomass negatively affected the CBCT image quality, they had no adverse effect on the diagnostic accuracy of CBCT for detection of vertical root fractures [37]. is difference is probably due to the use of different types of scanners and optimized exposure settings applied in their study.…”
Section: Discussionmentioning
confidence: 86%
“…us, high atomic number and high physical density increase artifact generation when exposed to X-ray radiation [6,29], and this increase is directly proportionate to the change in GV. Increased variability in GV indicates greater effects of artifacts on CBCT images, and subsequent reduction of image quality [27,37].…”
Section: Discussionmentioning
confidence: 99%
“…However, activation of the MAR mode obviously resulted in more accurate diagnosis of the simulated implant fractures (AUC = 0.917 for MAR on mode vs. AUC = 0.875 for MAR off mode). Kajan et al and Candemil et al, also observed that application of the MAR tool in the CBCT images enhances the detectability of vertical root fractures particularly when the teeth contain intracanal metallic posts 34 – 36 .…”
Section: Discussionmentioning
confidence: 97%
“…Despite the excellent diagnostic accuracy of CBCT, this imaging method needs some caution; for example, field of view adjustment should be considered, to use the lowest radiation dose possible on the patients [ 25 - 27 ]. According to the latest statement of American Association of Endodontists/American Academy of Oral and Maxillofacial Radiology Position, CBCT imaging should be the method of choice for diagnosing patients presenting with conflicting or nonspecific clinical signs and symptoms [ 28 ].…”
Section: Discussionmentioning
confidence: 99%